The economic crisis in Portugal and children’s rights to non-discrimination - Sarmento, Manuel Jacinto (2014)
The consequences that arose from the ‘global economy’ have been significant in Portuguese children’s lives and we believe it is fundamental to reflect on the ongoing structuring of childhood through this global culture/ideology and the concrete implications that they have. It is also important to understand how childhood is constructed and experienced, as well as to consider the impacts of political economic conditions on children’s lives and in childhood in general, taking into account the effects brought on by public policies. The aim of this paper is to reflect on the ways through which the economic crisis affecting the general Portuguese population has impacted children in particular and promoted discrimination and a lack of opportunities in childhood. We will focus on two dimensions: first, on general data about the ongoing policies that have been reducing social rights, increasing poverty rates and threatening basic rights such as educational and health rights, to show their impact on children´s lives. Second, we will discuss some data collected with children throughout different research projects in order to characterize the meanings and impacts of the crisis in their lives from their points of view